A proximal progressive resistance training program targeting strength and power is feasible in people with patellofemoral pain - Barton, Christian J.; de Oliveira Silva, Danilo [UNESP]; Patterson, Brooke E.; Crossley, Kay M.; Pizzari, Tania; Nunes, Guilherme S. (Elsevier, 2019)
Objectives: To evaluate the feasibility of a 12-week progressive resistance training program for people with patellofemoral pain (PFP) targeting proximal muscle strength and power; and resulting clinical and muscle capacity outcomes. Design: Feasibility study. Setting: Clinical environment. Participants: Mixed-sex sample of people with PFP. Main outcome measures: Feasibility outcomes included eligibility, recruitment rate, intervention adherence, and drop-outs. Secondary outcomes included perceived recovery, physical function (AKPS and KOOS-PF), worst pain (VAS-cm), kinesiophobia (Tampa), physical activity (IPAQ), and hip strength (isometric and 10 repetition maximum) and power. Results: Eleven people, from 36 who responded to advertisements, commenced the program. One participant withdrew. Ten participants who completed the program reported improvement (3 completely recovered; 6 marked; and 1 moderate). Higher AKPS (effect size [ES] = 1.81), improved KOOS-PF (ES = 1.37), and reduced pain (ES = 3.36) occurred alongside increased hip abduction and extension dynamic strength (ES = 2.22 and 1.92, respectively) and power (ES = 0.78 and 0.77, respectively). Isometric strength improved for hip abduction (ES = 0.99), but not hip extension. Conclusion: A 12-week progressive resistance training program targeting proximal muscle strength and power is feasible and associated with moderate-large improvements in pain, function, and hip muscle capacity in people with PFP. Further research evaluating the efficacy of progressive resistance training is warranted.
Keywords: Exercise; Patellofemoral; Power; Strength